The Development of Interactive Reading Digital Module with Contextual Approach for BIPA International School Students - Meiruly, Vietcia; Idris, Nuny Sulistiany; Sundusiah, Suci (Jurnal Pendidikan Bahasa dan Sastra, 2024)
Teaching BIPA (Indonesian for Foreign Speakers) in SPK (Satuan Pendidikan Kerjasama) has its polemics. Based on the needs analysis, one of them is that not all BIPA learners in SPK exhibit enthusiasm toward engaging with Indonesian reading materials. This displeasure comes from several factors including a general disinterest in reading, a lack of motivation to utilize the Indonesian language beyond the confines of language classes, and other obstacles like unappealing teaching materials. Thereby, this research aims to develop an Interactive Reading digital Module based on Contextual Approach in SPK. This research uses the RD method with the ADDIE Model design and has evaluation sessions at each stage. This article will focus on the developing stage and show validation results from the expert validators. The results showed that based on expert validators, the interactive reading digital module can be used with the material, media design feasibility percentage of 83% of eligible excellent predicate.